PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY MATERISEGIEMPAT DAN SEGITIGA KELASVII SMPN 1 BASO - RIRIN RIZKIYANTI MEYSI (Departemen Matematika, 2021)
The research try to aims to develop a learning tool in the form of Student Worksheets on the material of squares and triangles for class VII in the Two Stay Two Stray type of cooperative learning model which is valid and practical.This development research uses the Plomp development model which consists of three stages, namely the initial investigation phase, the development phase, and the assessment phase.Validation is carried out by mathematics education experts and language experts. The practicality of Student Worksheets is seen from the practicality questionnaire results of the student response questionnaire. The research conducted shows that Student Worksheets in theTwo Stay TwoStray type of cooperative learning model has met the valid criteria in terms of content and construct. Student Worksheets is practical in terms of implementation, convenience and time needed in mathematics learning activities. Based on these results, it can be concluded that the Student Worksheets in the Two Stay Two Stray type of cooperative learning model for grade VII junior high school students of the squares and Triangles material that has been produced can be declared valid and practical.Keywords__Development Research, Student Worksheet, Two Stay Two Stray, Squares and Triangles